1985
DOI: 10.1002/1098-108x(198511)4:4<511::aid-eat2260040411>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Sense of ineffectiveness in women with eating disorders: A clinical study of anorexia nervosa and bulimia

Abstract: In the present study, equal numbers of patients with anorexia nervosa and bulimiawere compared with noneating‐disordered control subjects on the Block Ego Control Scale, Adjective Check List Autonomy Scale, and Embedded Figures Test. The anorexics displayed significantly greater ridigity of control than the noneating‐disordered subjects, whereas the bulimics could not be distinguished from either of the other two groups on this dimension. Although there were no group differences in self‐ascribed level of auton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Other self-control defecits, however, were supported: there was a tendency for HEDI scorers to be less likely to attribute their performance to ability and more likely to attribute good performance to effort and situational factors. With the exception of effort attributions, this tends to be in line with studies which have shown that people with eating problems are more influenced in their behavior and beliefs by external as opposed to internal factors (Garfinkel, 1981;Mclaughlin et al, 1985;Weiss & Ebert, 1983).…”
Section: Disc U Sslonsupporting
confidence: 86%
“…Other self-control defecits, however, were supported: there was a tendency for HEDI scorers to be less likely to attribute their performance to ability and more likely to attribute good performance to effort and situational factors. With the exception of effort attributions, this tends to be in line with studies which have shown that people with eating problems are more influenced in their behavior and beliefs by external as opposed to internal factors (Garfinkel, 1981;Mclaughlin et al, 1985;Weiss & Ebert, 1983).…”
Section: Disc U Sslonsupporting
confidence: 86%
“…Such differences in personality style (e.g., social acting out versus social isolation) are compatible with no differences in level of ego pathology. In the same vein, McLaughlin, Karp, and Herzog (1985) concluded that both anorexics and bulimics manifested similar deficits in self-directed autonomy, but that anorexics used a rigid overcontrolling ego style to compensate for it, whereas bulimics were more impulsive in their ego styles. The observation by Johnson and Connors (1987) concerning maternal overinvolvement versus underinvolvement in the child producing restricting versus bulimic adaptation to a similar basic psychopathology also seems to point in the same direction.…”
Section: Discussionmentioning
confidence: 99%
“…McLaughlin et al. () found that patients with anorexia nervosa did not differ from healthy controls in terms of self‐ascribed autonomy (i.e., taking action, regardless of other people's evaluations). Correspondingly, Strauss and Ryan () did not find differences between patients with anorexia nervosa and healthy controls regarding self‐reported interpersonal autonomy (i.e., perceiving others as autonomy‐supporting or not).…”
Section: Potential Precursors Of Autonomy Disturbances In Anorexia Nementioning
confidence: 99%
“…Correspondingly, Strauss and Ryan () did not find differences between patients with anorexia nervosa and healthy controls regarding self‐reported interpersonal autonomy (i.e., perceiving others as autonomy‐supporting or not). However, McLaughlin et al () showed that patients with anorexia nervosa as well as patients with bulimia nervosa were more field‐dependent. Field dependence was considered as “the tendency for perception to be dominated by the overall organization of the field, so that parts of the field are experienced as fused” (McLaughlin et al., , p. 516).…”
Section: Potential Precursors Of Autonomy Disturbances In Anorexia Nementioning
confidence: 99%